2020
DOI: 10.31234/osf.io/zvs9f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Depression, Environmental Reward, Coping Motives and Alcohol Consumption During the COVID-19 Pandemic

Abstract: Increases in the incidence of psychological distress and alcohol use during the COVID-19 pandemic have been predicted. Environmental reward and self-medication theories suggest that increased distress and greater social/environmental constraints during COVID-19 could result in increases in depression and drinking to cope with negative affect. The current study had two goals: (1) to clarify the presence and direction of changes in alcohol use and related outcomes after the introduction of COVID-19 social distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 52 publications
2
50
0
2
Order By: Relevance
“…Self-medication theory posits that stress may overburden individuals’ coping resources and increase reliance on substances to cope, which in turn contributes to the development of problematic use ( Khantzian, 1997 ). Consistent with self-medication theory, COVID anxiety and elevations in anxious and depressive symptoms during the pandemic have been linked to elevations in SU and coping motives ( Lechner et al, 2020 ; McPhee et al, 2020 ). While these studies provide important insights, they have not examined how COVID anxiety and anxious/depressive symptoms may prospectively predict further elevations in SU, coping motives, or consequences of use as the pandemic progresses.…”
Section: Introductionmentioning
confidence: 72%
“…Self-medication theory posits that stress may overburden individuals’ coping resources and increase reliance on substances to cope, which in turn contributes to the development of problematic use ( Khantzian, 1997 ). Consistent with self-medication theory, COVID anxiety and elevations in anxious and depressive symptoms during the pandemic have been linked to elevations in SU and coping motives ( Lechner et al, 2020 ; McPhee et al, 2020 ). While these studies provide important insights, they have not examined how COVID anxiety and anxious/depressive symptoms may prospectively predict further elevations in SU, coping motives, or consequences of use as the pandemic progresses.…”
Section: Introductionmentioning
confidence: 72%
“…Time‐invariant covariates were gender (Grucza et al, 2018), having children under the age of 18 at home (Wardell et al, 2020), race (categorized as White, Black, Asian, or other), and Hispanic ethnicity (Meyers et al, 2017). Time‐varying covariates were respondents’ age (Grucza et al, 2018), employment status (Collins, 2016; Frone, 2008), and a dichotomous measure of whether or not they reported avoiding public spaces to avoid disease risk at the time of each survey, as social distancing may be related to frequency of consumption (McPhee et al, 2020). We additionally include two mental health covariates, depression and anxiety, both of which are associated with alcohol consumption (Marmorstein, 2009; McHugh and Weiss, 2019; Smith and Randall, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…A sample of US college students—a population normally at elevated risks of alcohol consumption—endorsed higher levels of alcohol consumption after university closure due to COVID‐19 than in the weeks before, with students reporting anxiety and depression symptomology reporting the highest increases (Lechner et al, 2020). Further, solitary drinking (i.e., drinking alone rather than with other people) increased among people who reported social distancing—that is, decreasing the frequency of contact and increasing the physical space between individuals—compared with retrospective recall of their drinking behaviors prior to social distancing (McPhee et al, 2020). Regarding coping, findings from a Canadian sample showed that alcohol consumption frequency and solitary drinking increased during the pandemic relative to the month prior to the pandemic and that drinking as a way to cope with stress was a major contributor to these changes (Wardell et al, 2020).…”
mentioning
confidence: 99%
“…A summary of studies from different countries (China, Finland, Belgium, Chile, US, Poland) reports increased alcohol consumption during lockdown compared to prelockdown [ 22 , 24 , 26 30 ]. Specifically, many studies report an increase in binge drinking, as well as solitary drinking [ 27 , 29 , 31 , 32 ▪ , 33 , 34 ]. Although some studies observed an increase in drinking among women [ 27 , 35 ], others did not observe gender differences in alcohol use patterns [ 36 ].…”
Section: Text Reviewmentioning
confidence: 99%